The psychological impact of cardiovascular screening in young athletes: Perspectives across age, race, and gender - Asif, I. M.; Price, D.; Harmon, K. G.; Salerno, J. C.; Rao, A. L.; Drezner, J. A. (Clinical Journal of Sport Medicine, 2015)
Objective: To determine the psychological impact of electrocardiogram (ECG) screening in young competitive athletes based on age, race, and gender.